A method for in-situ synthesis of carbon nanotube-based ternary adsorption catalytic material in a fluidized bed
Patent Information
- Application Number
- CN202611361364.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]针对现有技术中低浓度异味VOCs治理成本高、高温工艺安全风险大,传统碳基催化材料高温制备损毁载体、活性组分硬团聚、VOCs矿化不彻底等缺陷,本发明提供一种光流化床两步流化光照原位制备CNT负载Ti-Ce-Pd三元吸附催化材料的低温合成工艺,同时提供该材料在低浓度恶臭VOCs一体化吸附-原位光热降解中的应用,实现以下目标:
1.工况适配性强,消除安全与成本短板
Smart Images

Figure CN122999291A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the interdisciplinary field of air pollution control, low-concentration VOCs adsorption and catalytic purification, and nanocomposite catalytic material preparation technology. Specifically, it relates to a low-temperature photofluidized bed preparation method of carbon nanotube (CNT) supported titanium-cerium-palladium ternary photothermal adsorption catalytic material, and its application in the deep degradation of large-volume, low-concentration odorous VOCs in the petrochemical industry. Background Technology
[0002] The exhaust gases emitted from petroleum and petrochemical, fine chemical, and wastewater treatment plants are characterized by large flow rates, low concentrations, and strong odors. Existing mainstream VOCs treatment technologies have significant drawbacks. Traditional regenerative catalytic oxidation (RCO / RTO) systems cannot sustain combustion due to the low VOCs concentration in the exhaust gas, requiring continuous natural gas replenishment. This results in extremely high operating costs for reagents and fuel gas. Furthermore, the equipment operates at high temperatures for extended periods, and petrochemical exhaust gases contain flammable and explosive light hydrocarbons, posing significant safety hazards and limiting their applicability. Single activated carbon adsorption processes enrich VOCs through physical adsorption alone, lacking degradation capabilities. After adsorption saturation, offline high-temperature desorption and regeneration are required, a complex process. The high-concentration exhaust gas generated during desorption still requires downstream combustion treatment, easily leading to secondary odor pollution. Conventional single photocatalytic materials (TiO2 / carbon materials) rely solely on ultraviolet light oxidation, resulting in low molecular oxygen activation efficiency, incomplete VOCs mineralization, and the generation of intermediate odorous byproducts such as aldehydes and ketones during the reaction process, failing to meet the standards for deep odor purification.
[0003] Carbon nanotubes (CNTs) possess ultra-high specific surface area and hollow tubular channels, making them ideal adsorption carriers for VOCs. However, existing preparation processes for carbon nanotube-supported metal oxide catalysts have significant drawbacks: conventional impregnation-calcination and hydrothermal synthesis processes require high-temperature heat treatment above 400℃, which easily leads to oxidation and ablation of carbon nanotubes and pore collapse, resulting in a significant decrease in adsorption capacity. Furthermore, high-temperature sintering causes metal oxide particles to agglomerate, drastically reducing the number of exposed active sites. On the other hand, traditional liquid-phase static impregnation and precipitation methods result in slow precursor precipitation rates, and metal hydroxide particles adhere to each other to form micron-sized aggregates, making it impossible to achieve monodisperse loading of active components and significantly reducing catalytic oxidation activity.
[0004] Existing Ti-Ce-Pd composite catalysts are mostly prepared by powder blending and high-temperature solid-state sintering, lacking a low-temperature photofluidized bed fluidized stepwise in-situ loading process; they cannot achieve uniform monodisperse anchoring of the Ti-Ce-Pd ternary components without damaging the carbon nanotube adsorption framework; existing technologies have not constructed a closed-loop cyclic mineralization mechanism of "Ti mineralization consuming lattice oxygen + Ce-Pd photothermal synergistic replenishment of lattice oxygen", resulting in insufficient degradation efficiency and in-situ regeneration performance for low-concentration VOCs.
[0005] In summary, the industry urgently needs a new carbon-based ternary adsorption catalytic material that is non-sintering at room temperature, has monodisperse active components, and combines adsorption enrichment with in-situ photothermal catalytic mineralization at room temperature, to be suitable for the safe and low-cost treatment of large-flow, low-concentration odorous VOCs in the petrochemical industry. Summary of the Invention
[0006] To address the shortcomings of existing technologies in treating low-concentration odorous VOCs, such as high costs, significant safety risks associated with high-temperature processes, and the damage to the carrier, hard agglomeration of active components, and incomplete VOCs mineralization during the high-temperature preparation of traditional carbon-based catalytic materials, this invention provides a low-temperature synthesis process for the in-situ preparation of CNT-supported Ti-Ce-Pd ternary adsorption catalytic materials via a two-step fluidized bed irradiation method. Simultaneously, it provides the application of this material in the integrated adsorption-in-situ photothermal degradation of low-concentration malodorous VOCs, achieving the following objectives: (1) The entire process is prepared by low-temperature liquid-phase photochemical process without high-temperature sintering, which completely preserves the high specific surface area adsorption channels of carbon nanotubes and does not reduce the adsorption capacity. (2) In-situ photocuring in a photofluidized bed inhibits the aggregation of active components and enables Ti-Ce-Pd nanoparticles to be monodispersed and anchored on the carbon nanotube wall; (3) Construct a Ti-Ce-Pd ternary photothermal synergistic lattice oxygen cycle mineralization system, enrich low concentration VOCs at room temperature and completely mineralize them in situ into CO2 and H2O, without the need for natural gas supplementation and high temperature conditions, thus eliminating the risk of combustion and explosion in the petrochemical industry. (4) The material has both strong adsorption and enrichment and in-situ catalytic self-regeneration functions, and can be used for a long time, which greatly reduces the cost of operation and maintenance of waste gas treatment.
[0007] According to one aspect of the present invention, an object of the present invention is to provide a method for preparing carbon nanotube-based ternary adsorption catalytic materials by in-situ synthesis in a photofluidized bed, comprising the following steps: Step 1: Oxidation modification of carbon nanotube surface Purified carbon nanotubes were dispersed in an aqueous hydrogen peroxide solution, soaked and stirred at room temperature, and then filtered and dried to obtain modified carbon nanotubes (CNTs) for later use. The etching effect of hydrogen peroxide was used to introduce hydroxyl and carboxyl oxygen-containing functional groups in situ into the CNT tube wall, providing uniform anchoring sites for the metal precursor and improving the binding strength of the active components.
[0008] Step 2: Active layer of Ti substrate loaded in optical fluidized bed (2.1) Preparation of precursor solution: Mix Ti(OH)4 solution with hydrogen peroxide aqueous solution to prepare a homogeneous and stable Ti-hydrogen peroxide complex solution; then add the modified carbon nanotube powder obtained in step 1) and stir to form a precursor mixture; (2.2) In-situ photocuring: The precursor mixture obtained in step 2.1) is added to a fluidized bed chamber equipped with an ultraviolet light source. The fluidizing gas is turned on to keep the precursor powder in a suspended fluidized state. During the fluidization process, the light is continuously irradiated simultaneously. The precursor undergoes photo-oxidation reaction in situ on the CNT tube wall, and the nano-TiO2 is uniformly anchored on the surface of the carbon nanotube, effectively avoiding particle agglomeration. After the fluidized light irradiation reaction for 1~2 hours, CNT@TiO2 intermediate powder is obtained. Step 3: Co-loading Ce and Pd components in an optical fluidized bed to synthesize a Ti-Ce-Pd ternary composite adsorption catalytic material. (3.1) Preparation of Ce-Pd precursor: Ce precursor and Pd precursor were mixed in hydrogen peroxide aqueous solution and stirred evenly. The CNT@TiO2 intermediate powder dispersion system prepared in step 2) was added to it and mixed to obtain CNT@TiO2-Ce-Pd composite precursor. (3.2) Secondary photofluidized bed loading: The above precursor is added to the photofluidized bed cavity and kept in a suspended fluidized state. It is simultaneously illuminated throughout the process to induce in-situ deposition. The fluidized light reaction lasts for 1-2 hours. The light excites hydrogen peroxide to generate active free radicals, which promote the in-situ conversion of Ce-Pd precursor into nano Pd and cerium oxide, and uniformly coats and anchors them on the TiO2 surface to form a tightly coupled Ti-Ce-Pd ternary composite nano active layer, and finally obtains the target product.
[0009] Preferably, in step 1), the solid-liquid ratio of carbon nanotubes to H2O2 is 1:0.5 to 1:10, more preferably 1:0.5 to 1:5, and even more preferably 1:1. When the solid-liquid ratio is less than 1:0.5, the amount of H2O2 is insufficient, the CNTs cannot be fully wetted, oxidation is uneven, the surface functional group density is low, the number of subsequent anchoring points is insufficient, and the final loading strength of the active component decreases. When the solid-liquid ratio is greater than 1:10, the excessive H2O2 solution causes the CNTs to be over-oxidized and etched, resulting in too many defects on the tube wall and even destruction of the framework structure. In addition, the amount of waste liquid increases, and the post-processing burden is increased.
[0010] Preferably, the mass percentage concentration of the hydrogen peroxide aqueous solution in step 1) is 20% to 30%, more preferably 25%. When the concentration is less than 20%, the effective oxidant content is insufficient, the ·OH free radical yield is low, the degree of CNT oxidation modification is insufficient, the amount of surface functional groups introduced is small, and the anchoring effect on the active component is poor. When the concentration is greater than 30%, the H2O2 concentration is too high, the oxidation reaction is too violent, the CNT tube wall is severely etched or even broken, the integrity of the carbon skeleton is destroyed, and the transportation, storage and handling of high-concentration H2O2 are more dangerous.
[0011] Preferably, the soaking and stirring time in step 1) is 2-4 hours.
[0012] Preferably, in step 2.1), the molar ratio of Ti(OH)4 to H2O2 is 1:5 to 1:50, more preferably 1:10 to 1:30, and even more preferably 1:20. When the molar ratio is less than 1:5, the amount of H2O2 is insufficient, and Ti... 4+ Incomplete complexation leads to the easy hydrolysis and condensation of Ti(OH)4, forming large precipitate particles. The precursor solution is uneven, resulting in severe agglomeration of TiO2 particles during subsequent loading. When the molar ratio is greater than 1:50, there is too much excess H2O2, which not only wastes reagents but also generates a large number of free radicals during subsequent ultraviolet irradiation. This causes TiO2 crystal nuclei to form explosively, making it difficult to control the particle size. Furthermore, the excess H2O2 increases the cost of raw materials and the burden of subsequent system processing.
[0013] Preferably, the mass percentage concentration of the Ti(OH)4 solution in step 2.1) is 3% to 15%, more preferably 6.5% to 7.5%. When the concentration is less than 3%, the Ti content is too low, the single loading capacity is small, multiple repeated operations are required, and the production efficiency is low; when the concentration is greater than 15%, the Ti(OH)4 concentration is too high, and Ti... 4+ It is easily hydrolyzed and condensed to form large particles, and its complexation with H2O2 is uneven, resulting in poor stability of the precursor solution.
[0014] Preferably, in step 2.1), the solid-liquid ratio of the modified CNT to the precursor liquid is 1:1 to 1:30, more preferably 1:1 to 1:5, and even more preferably 1:2.5. When the solid-liquid ratio is less than 1:1, the liquid volume is too small, the CNT powder cannot be fully wetted, the precursor loading is uneven, and some CNT surfaces cannot form a TiO2 coating layer. When the solid-liquid ratio is greater than 1:30, the liquid volume is too large, the slurry is too fluid, the CNT is suspended in a large amount of liquid, the subsequent fluidized bed feed has a large liquid volume and a heavy drying burden, and the precursor is homogeneously nucleated in the liquid phase rather than loaded onto the CNT surface, resulting in low loading efficiency.
[0015] Preferably, the fluidizing gas used in step 2.2) is air or nitrogen.
[0016] Preferably, the ultraviolet irradiation conditions in step 2.2) are 254 nm and 0.1 mW / cm². 2 Up to 1.5mW / cm 2 Continuous ultraviolet light irradiation, with a light intensity preferably of 0.1 mW / cm². 2 Up to 0.8mW / cm 2 More preferably 0.4 mW / cm 2 When the light intensity is less than 0.1 mW / cm 2 When the photon flux is insufficient, the photolysis rate of H2O2 is low, the yield of ·OH radicals is low, the driving force for TiO2 crystallization is weak, the reaction rate is slow, and the degree of product crystallization is low; when the light intensity is greater than 1.5 mW / cm 2When the light intensity is too high, H2O2 decomposes rapidly and generates a large number of bubbles that interfere with the fluidization state. This also increases the risk of local overheating, and CNTs may suffer photochemical damage.
[0017] Preferably, the temperature of the reaction system in step 2.2) is controlled to be less than or equal to 80°C, and more preferably between 40°C and 80°C. When the temperature is less than 40°C, the reaction rate is slow, the photo-crystallization time needs to be extended, and the production efficiency is reduced; when the temperature is greater than 80°C, the thermal decomposition of H2O2 intensifies, a large amount of reagents are decomposed and lost without participating in the reaction, the utilization rate decreases, and water evaporates in large quantities when the temperature is close to 100°C, the system loses water and affects the normal progress of the reaction.
[0018] Preferably, the Ce precursor in step 3.1) is selected from Ce(OH)4, hydrochloride, and nitrate.
[0019] Preferably, the Pd precursor in step 3.1) is selected from hydrochloride, nitrate, or sulfate.
[0020] Preferably, in step 3.1), the molar ratio of Ce:Pd:H2O2 is 0.1-10:0.1:10-50, more preferably 1-10:0.1:10-40, and even more preferably 5:0.1:20. When the molar ratio of Ce to Pd is less than 0.1, the Ce content is too low, the oxygen storage capacity is insufficient, and it cannot effectively replenish the lattice oxygen consumed by TiO2, resulting in poor self-regeneration ability of the catalyst lattice oxygen. When the molar ratio of Ce to Pd is higher than 10, the Ce content is too high, the Pd active sites are excessively diluted, and the excessively generated CeO2 may cover the photoactive sites of TiO2, reducing photocatalytic efficiency. When the molar ratio of H2O2:Ce is less than 10, H2O2 is insufficient, and Ce... 4+ and Pd 2+ Incomplete complexation reaction leads to easy hydrolysis and precipitation of the precursor, resulting in uneven loading. When the molar ratio of H2O2 to Ce is greater than 50, H2O2 is in severe excess, generating too many free radicals during subsequent light irradiation, causing the reaction to run out of control and wasting reagents.
[0021] Preferably, the solid-liquid ratio of the CNT@TiO2 intermediate powder added in step 3.1) to the system is 1:1 to 1:10, more preferably 1:1 to 1:5, and even more preferably 1:2.5. When the solid-liquid ratio is less than 1:1, the liquid volume is insufficient, resulting in uneven wetting and uneven Ce-Pd loading; when the solid-liquid ratio is greater than 1:10, the liquid volume is excessive, causing the Ce-Pd precursor to homogeneously nucleate in the liquid phase instead of being loaded onto the CNT@TiO2 surface, resulting in low loading efficiency and a large liquid burden during fluidized bed processing.
[0022] Preferably, the fluidizing gas used in step 3.2) is air or nitrogen.
[0023] Preferably, the ultraviolet irradiation conditions in step 3.2) are 254 nm and 0.1 mW / cm². 2 Up to 1.5mW / cm 2 Continuous ultraviolet light irradiation, with a light intensity preferably of 0.1 mW / cm². 2 Up to 0.8mW / cm 2 More preferably 0.4 mW / cm 2 .
[0024] Preferably, in step 3.2), the temperature of the entire reaction system is controlled to be less than or equal to 80°C, and more preferably between 40°C and 80°C.
[0025] According to another aspect of the present invention, another object of the present invention is to provide a carbon nanotube-based ternary adsorption catalyst, said catalyst being prepared by the above-described preparation method.
[0026] According to another aspect of the invention, another object of the invention is to provide the application of the catalyst in the catalytic degradation of large-volume, low-concentration VOC waste gas from petrochemical processes.
[0027] Beneficial effects 1. High adaptability to various working conditions, eliminating safety and cost shortcomings. For the petrochemical industry, which deals with large-volume, low-concentration, flammable, and explosive VOCs with odors, this invention employs room-temperature adsorption-in-situ photothermal catalytic degradation, eliminating the need for combustion supplementary natural gas and completely eliminating gas costs. At the same time, the entire process operates without high-temperature equipment, fundamentally avoiding the safety hazards of light hydrocarbon waste gas combustion and explosion in high-temperature environments, thus ensuring production safety.
[0028] 2. Dual enhancement of adsorption and catalytic performance This invention utilizes a low-temperature reaction throughout the entire process, perfectly preserving the integrity of the carbon nanotube framework. This results in a VOCs dynamic adsorption capacity far exceeding that of high-temperature sintered carbon-based catalysts. Through the optical fluidized bed effect, the Ti-Ce-Pd active components achieve high monodispersity, with a VOCs degradation and mineralization rate ≥98%. Furthermore, this material can completely oxidize odorous substances without emitting toxic intermediate byproducts such as aldehydes and ketones, meeting stringent odor pollutant emission standards.
[0029] 3. The material can be recycled in situ, resulting in a long service life. The catalyst of this invention has excellent self-regeneration capability. When VOCs adsorption is saturated, it can be self-regenerated by relying on lattice oxygen cycling under continuous light irradiation, without the need for offline high-temperature desorption. The Ti-Ce-Pd synergistic oxygen storage and release structure endows the material with excellent anti-carbon deposition and anti-poisoning properties. Its continuous stable operation time is more than 3 times that of single TiO2 / carbon materials, reducing replacement frequency and operating costs.
[0030] 4. The preparation process is green and easy to scale up industrially. The low-temperature photofluidized bed synthesis process employed in this invention eliminates the need for a high-temperature tubular furnace. The hydrogen peroxide and acid / base reagents used in the process can be easily recycled, resulting in zero high-temperature waste gas and residue emissions throughout the entire process, and low energy consumption. This process is simple, controllable, and suitable for large-scale mass production.
[0031] 5. Wide range of applications Based on the above-mentioned excellent properties, the material prepared by this invention has extremely strong versatility and can be widely used in various low-concentration VOCs treatment scenarios such as exhaust gas from petroleum and petrochemical plants, odor from chemical wastewater treatment plants, low-concentration organic waste gas from painting, and odor from printing workshops, and has extremely high market promotion value. Attached Figure Description
[0032] Figures 1A to 1C This is a transmission electron microscope image of the carbon nanotube-supported TiO2-Ce-Pd catalyst prepared in Example 1.
[0033] Figure 2 This is a schematic diagram of the reaction mechanism of low-concentration VOCs mineralization in the lattice oxygen cycling of the ternary Ti-Ce-Pd system according to the preparation method of the present invention.
[0034] Figure 3 The graph shows the VOCs adsorption-degradation performance comparison between the catalysts prepared in Examples 1 to 3 and the catalyst prepared in Comparative Example 1. Detailed Implementation
[0035] Preferred embodiments of the present disclosure will be described in detail below with reference to the accompanying drawings. Before description, it should be understood that the terminology used in the specification and appended claims should not be construed as limited to its general and dictionary meaning, but rather should be interpreted based on the principle of allowing the inventors to appropriately define the terminology for the best interpretation, and based on its meaning and concept corresponding to the technical level of the invention. Therefore, the description herein is merely a preferred example for illustrative purposes and is not intended to limit the scope of the invention; thus, it should be understood that other equivalent implementations and modifications can be made without departing from the spirit and scope of the invention.
[0036] In this document, the terms “comprising,” “including,” “having,” “containing,” or any other similar terms are open-ended conjunctions intended to cover non-exclusive inclusions. For example, a composition or article containing a plurality of elements is not limited to those listed herein, but may also include other elements not explicitly listed but typically inherent to the composition or article. Furthermore, unless explicitly stated to the contrary, the term “or” is inclusive, not exclusive. For example, the condition “A or B” is satisfied in any of the following cases: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); A and B are both true (or exist). Moreover, in this document, the terms “comprising,” “including,” “having,” and “containing” should be interpreted as specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as “composed of” and “substantially composed of.”
[0037] In this document, all features or conditions defined in the form of numerical ranges or percentage ranges are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible secondary ranges and individual values within those ranges, particularly integer values. For example, a range description of "1 to 8" should be considered as specifically disclosing all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., particularly secondary ranges defined by all integer values, and should be considered as specifically disclosing individual values within those ranges such as 1, 2, 3, 4, 5, 6, 7, 8, etc. Unless otherwise specified, the foregoing interpretation applies to all content throughout this invention, regardless of its scope.
[0038] If a quantity or other numerical value or parameter is expressed as a range, a preferred range, or a series of upper and lower limits, it should be understood that this document has specifically disclosed all ranges consisting of any upper or preferred value of that range and the lower or preferred value of that range, regardless of whether such ranges are separately disclosed. Furthermore, when a range of numerical values is mentioned herein, unless otherwise stated, the range shall include its endpoints and all integers and fractions within the range.
[0039] In this document, numerical values are to be understood as having a precision with significant digits, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.
[0040] The catalyst material prepared according to the method of the present invention constructs a unique Ti-Ce-Pd ternary component synergistic lattice oxygen cycling degradation mechanism, which is specifically designed for the efficient mineralization of low-concentration VOCs. Its core reaction mechanism is as follows: (1) Lattice oxygen activation: TiO2 active sites activate molecular oxygen in the air under low temperature photoexcitation to convert it into lattice active oxygen, which directly oxidizes and degrades low-concentration odor VOCs adsorbed and enriched in the carbon nanotube pores into CO2 and H2O; this process continuously consumes lattice oxygen, and the number of lattice oxygen vacancies increases. (2) Photothermal oxygen replenishment cycle: The CeO2-Pd composite component generates a local photothermal effect under light irradiation, which efficiently captures gaseous oxygen and transports it to the TiO2 lattice to replenish lattice oxygen and fill oxygen vacancies; (3) Synergistic long-term operation: Ti-Ce-Pd work together to promote the continuous regeneration of lattice oxygen. Under normal temperature and pressure conditions, low concentration VOCs can be continuously and completely mineralized without the accumulation of odorous intermediate products such as aldehydes and ketones. Simultaneously, VOCs adsorption and enrichment and in-situ self-regeneration are completed.
[0041] This invention abandons the traditional high-temperature calcination process and adopts a low-temperature optical fluidized bed synthesis route throughout the process, which effectively solves the industry pain points of high-temperature damage to carbon carriers and hard agglomeration of active components.
[0042] (1) Suppressing high temperature damage: There is no high temperature calcination process throughout the process, and the maximum processing temperature does not exceed 80℃, which fundamentally avoids the structural damage caused by carbon nanotube oxidation and ablation, pore collapse and other issues caused by traditional high temperature sintering. The resulting material has a VOCs dynamic adsorption capacity that is more than 40% higher than that of traditional high temperature processes. (2) Suppressing hard agglomeration of particles: After mixing the precursor solution with carbon nanotubes to obtain wet powder, it is fed into a photofluidized bed. With the help of the continuous fluidization effect of the fluidized bed and the in-situ photodeposition mechanism, combined with the complexation inhibition effect of hydrogen peroxide, the precursor will not agglomerate and precipitate on a large scale during the reaction. The resulting Ti-Ce-Pd nano-active particles can be uniformly and monodispersedly anchored on the carbon nanotube wall, which greatly improves the exposure of active sites.
[0043] This invention pioneered a stepwise optical fluidized bed loading process, successfully constructing a ternary tightly coupled structure with TiO2 as the substrate and Ce-Pd as the surface layer, overcoming the defect of weak interfacial bonding in existing technologies.
[0044] (1) Step-by-step anchoring strategy: First, TiO2 is anchored as the basic photo-oxidation layer, and then Ce-Pd oxygen storage components are loaded in the in-situ photo-fluidized bed environment.
[0045] (2) Enhanced synergistic effect: This stepwise process enables the formation of a tight interfacial bond between the ternary components, simultaneously achieving the dual-function integration of molecular oxygen activation and lattice oxygen storage and replenishment. Compared with the one-step blending and loading method commonly used in the prior art, this invention effectively solves the problems of poor interfacial bonding and weak synergistic effect of the ternary components.
[0046] This invention constructs a unique Ti-Ce-Pd ternary photothermal synergistic lattice oxygen closed-loop mineralization mechanism, which is suitable for the room temperature deep degradation of low-concentration, malodorous VOCs.
[0047] (1) Lattice oxygen closed-loop circulation system: Unlike conventional single photocatalysis which relies on free radical oxidation and is prone to incomplete mineralization, this system relies on the lattice oxygen circulation path to achieve efficient mineralization of VOCs. It can degrade low-concentration odorous VOCs at room temperature and does not require natural gas supplementary combustion, thus avoiding the risk of high-temperature combustion and explosion of petrochemical waste gas from the source.
[0048] (2) Integrated adsorption-catalytic regeneration function: It realizes the high coupling and integration of adsorption and catalytic regeneration, which greatly reduces the operation and maintenance cost of waste gas treatment, and there is no accumulation of odorous intermediate products such as aldehydes and ketones.
[0049] This invention develops an integrated additive system based on hydrogen peroxide modification, complexation, and photo-oxidation, achieving precise control over the entire process of carrier modification and active component loading.
[0050] (1) Triple synergistic effect: Hydrogen peroxide has multiple functions in the preparation process: First, it is used for the oxidative modification of carbon nanotubes to build a rich number of anchoring sites; second, it acts as a complexing agent to stabilize metal precursors and inhibit their premature aggregation; finally, it decomposes under light to generate active free radicals, which induces the in-situ uniform deposition of metal oxides.
[0051] (2) Green circular process: Relying on this integrated auxiliary agent system, the preparation process can be greatly simplified, and the agent can be recycled and reused, which is in line with the concept of green chemical development.
[0052] Unless otherwise stated, the reagents and solvents disclosed below were purchased from Jiangsu Tiannai Technology Co., Ltd., Licheng District Bainachuan Chemical Business Department, Beijing Innocare Technology Co., Ltd., and Langfang Tuodi Chemical Co., Ltd.; the transmission electron microscope used was a JEOL JEM-F200 model from Japan, and the gas chromatograph used was a Shimadzu GC-2014 model from Japan.
[0053] Example 1 1. Carbon nanotube modification pretreatment: Add 25% hydrogen peroxide aqueous solution to carbon nanotube powder at a solid-liquid ratio of 1:1, soak and stir at room temperature for 3 hours to obtain modified carbon nanotubes (CNTs). 2. First step: Photofluidization loading of Ti: Ti(OH)4 solution (7.07%) was uniformly dispersed in hydrogen peroxide aqueous solution and stirred evenly according to the molar ratio n(Ti):n(H2O2) = 1:20 to prepare titanium hydroxide-hydrogen peroxide precursor solution; then, the pretreated modified CNT was mixed with the above precursor solution at a mass solid-liquid ratio of 1:2.5 to obtain precursor mixture; The precursor mixture obtained above was added to a fluidized bed chamber equipped with an ultraviolet light source. Fluidizing gas (air) was turned on to maintain the precursor powder in a suspended fluidized state. The wavelength was 254 nm and the ultraviolet light intensity was 0.4 mW / cm². 2 CNT@TiO2 powder was obtained by continuous ultraviolet light irradiation and fluidized bed irradiation for 1.5 hours, with the temperature of the reaction system controlled at ≤80℃ throughout the process. 3. Second step: Photofluidized loading of Ce-Pd: Ce(OH)4 suspension (54.62% by mass) and PdCl2 solution (0.1 mol / L) were mixed in hydrogen peroxide aqueous solution at a molar ratio of n(Ce):n(Pd):n(H2O2) = 5:0.1:20. An appropriate amount of H2O was added to replenish the mixture, and the mixture was stirred evenly to obtain Ce-Pd-H2O2 precursor mixture. The CNT@TiO2 powder dispersion system prepared above was added to the mixture at a solid-liquid ratio of 1:2.5 by mass and mixed evenly to obtain CNT@TiO2-Ce-Pd composite precursor. The composite precursor was placed in the photofluidized bed cavity and kept in a suspended fluidized state. Simultaneous ultraviolet light was applied for 2 hours to obtain the final target product. The temperature of the reaction system was controlled at ≤80℃ throughout the process. Performance testing: for 50mg / m³ 3 Low-concentration toluene odorous waste gas can achieve a pollutant degradation and mineralization rate of up to 99.2% under normal temperature conditions. After 120 hours of continuous cyclic operation, the material properties showed no significant degradation. The dynamic adsorption capacity is increased by 50% compared to the control sample prepared by the high-temperature impregnation method.
[0054] Example 2 (Shortening the light exposure time and reducing the hydrogen peroxide concentration) 1. Carbon nanotube modification pretreatment: Except for using a 20% hydrogen peroxide aqueous solution and adjusting the CNT modification time to 2 hours, the other operation steps are the same as the CNT modification pretreatment steps in Example 1. 2. First step: Optofluidizing Ti: Except for adjusting the illumination time to 1 hour, the other operation steps are the same as the optofluidizing Ti step in Example 1; 3. Second step: Optofluidization loading Ce-Pd: Except for adjusting the illumination time to 1 hour, the other operation steps are the same as the optofluidization loading Ce-Pd steps in Example 1; Performance testing: The prepared catalytic material exhibited a VOCs mineralization efficiency of 96.5%. Compared with the traditional high-temperature process used in Comparative Example 1, the dynamic adsorption capacity is increased by 43%, making it suitable for low-load waste gas treatment.
[0055] Example 3 (Increasing drug concentration and extending treatment time) 1. Carbon nanotube modification pretreatment: Except for using a 30% hydrogen peroxide aqueous solution and adjusting the CNT modification time to 4 hours, the other operation steps are the same as the CNT modification pretreatment steps in Example 1. 2. First step: Optofluidizing Ti: Except for adjusting the illumination time to 2h, the other operation steps are the same as the optofluidizing Ti step in Example 1; 3. Second step: Optofluidization loading Ce-Pd: Except for adjusting the illumination time to 2h, the other operation steps are the same as the optofluidization loading Ce-Pd steps in Example 1.
[0056] Performance testing: The prepared catalytic material achieved a mineralization rate of up to 99.6% for low-concentration odorous pollutants such as acetaldehyde and methanethiol; Compared with the traditional high-temperature process for preparing materials in Comparative Example 1, the dynamic adsorption capacity is increased by 61%, making it suitable for waste gas treatment applications with strict odor control and stringent emission limits.
[0057] Comparative Example 1 (Conventional co-impregnation-high temperature heat treatment process) 1. Acidification pretreatment of carbon nanotubes: Prepare a 20% nitric acid solution by volume, add carbon nanotubes at a solid-liquid ratio of 1:667 by mass, and stir at 70-90℃ for 4-6 hours; wash with deionized water until the filtrate is nearly neutral, and dry at 50-70℃ for 7-9 hours after washing to obtain acidified carbon nanotubes. 2. Multi-metal co-impregnation: Following the same molar ratio as in Example 1, Ti(OH)4 solution, Ce(OH)4 suspension, and PdCl2 solution were dissolved together in deionized water and stirred thoroughly at room temperature to prepare a Ti-Ce-Pd mixed metal precursor solution. The pretreated carbon nanotube powder was added to the above mixed precursor solution and impregnated by stirring continuously at room temperature for 8–12 hours. After impregnation, the solid phase was separated by filtration and dried in a forced-air oven at 100–110°C for 8–12 hours to remove free water, thereby obtaining a carbon nanotube intermediate loaded with metal salts. 3. Liquid-phase pre-reduction treatment: A compound liquid-phase reducing agent system (potassium borohydride, hydrazine hydrate, and sodium formate dissolved in ethylene glycol solvent) was prepared. The impregnated and dried carbon nanotube intermediate was added to the reduction system, and the mixture was continuously stirred and heated under reflux to pre-reduce the metal ions adsorbed on the surface of the carbon nanotubes. After the reaction was completed, the mixture was cooled to room temperature, filtered to collect the solid, thoroughly washed, and dried to obtain the catalyst precursor. 4. Segmented high-temperature heat treatment: The catalyst precursor was placed in a tube furnace, and nitrogen was continuously introduced as a protective gas; the temperature was programmed to rise to 300-500℃, and hydrogen was introduced to maintain the temperature for 3-5 hours for deep reduction; then the hydrogen was stopped, the nitrogen atmosphere was maintained, and the temperature was raised again to 300-500℃ and maintained for 1-2 hours; after the heat treatment was completed, the material was naturally cooled to room temperature under nitrogen protection to obtain the comparative example - carbon nanotube supported Ti-Ce-Pd ternary catalyst material.
[0058] Performance testing: Under the same working conditions, the sample has a VOCs mineralization rate of only 72%. Even with nitrogen protective atmosphere heat treatment, the simultaneous nucleation and growth of multi-metal precursors can easily lead to the aggregation of active components, and the interfacial bonding of ternary components is weak. If the heat treatment atmosphere is replaced with an air atmosphere, the high temperature of 500℃ will cause oxidation and ablation of the carbon nanotube wall and collapse of the pores.
[0059] Compared to the sample prepared in this invention, the dynamic adsorption capacity decreased significantly, and the catalyst deactivated due to carbon buildup after 8 hours of continuous operation.
[0060] References: [1] Qin Lizhen, Qian Fei, Zhang Tao. A modified carbon nanotube supported metal hydrogenation catalyst and its preparation method and application [P]. Chinese Patent: CN121060516A, 2025-12-05. [2] Ge Ming, Yuan Xiaolei, Xiao Kaiwen, et al. A carbon nanotube-supported ternary PtCoNi composite catalyst and its preparation method and application [P]. Chinese Patent: CN121983599A, 2026-05-05. Test Examples 1-3, Comparative Example 1 1. Using an electronic analytical balance with an accuracy of 0.1 mg, 50 mg of the catalyst samples prepared in Examples 1 to 3 and Comparative Example 1 were accurately weighed and carefully transferred to a metal reactor. At the same time, a toluene blank control group was set up. Except for the absence of catalyst sample, the reaction conditions in this group were kept consistent with those in the catalyst test group to eliminate the interference of factors such as toluene volatilization and reactor adsorption on the experimental results, and to ensure the accuracy and reliability of the test data.
[0061] 2. Construct a complete toluene adsorption-photocatalytic degradation testing system. Its core components include a toluene gas generator, a metal reactor, and a xenon lamp light source system (equipped with a 50mW power module and 26.6mW / cm²). 2 The apparatus consists of an intensity modulation assembly and a gas chromatograph (model GC-2014). Before the experiment, the airtightness of each connection should be checked, and then the pipeline should be purged with nitrogen for 30 minutes to eliminate interference from air in the pipeline on the detection of toluene concentration.
[0062] 3. Toluene gas was introduced into the reactor at a flow rate of 10 mL / min using a toluene gas generator for 17 hours. Simultaneously, air was introduced into the reactor at a flow rate of 40 mL / min to ensure that the initial toluene concentration in the reactor remained stable at 32.69 ppm. After the adsorption process reached equilibrium, the xenon lamp light source system was started for a 20-minute preheating operation.
[0063] 4. After preheating, align the xenon lamp light source with the center of the reactor and start the photocatalytic degradation timer. According to the experimental design, gas samples were automatically and continuously collected from the reactor every 25 minutes through the gas sampling port. The chromatographic peak area of toluene was recorded using a gas chromatograph workstation, and the toluene concentration at the corresponding time point was calculated using a standard curve. The sampling process lasted a total of 480 minutes, ultimately obtaining 21 sets of toluene concentration data (including the initial adsorption equilibrium concentration, the 0-minute illumination concentration, and subsequent concentration data every 25 minutes).
[0064] The toluene concentration data of the catalyst test group and the blank control group were organized in chronological order, and a "toluene concentration-time" curve was plotted. The curve of the catalyst test group reflects the concentration change of toluene under the synergistic effect of catalyst adsorption and photocatalysis, while the curve of the blank control group reflects the concentration change of toluene without catalyst. By comparing the degradation differences between the two sets of curves, the photocatalytic degradation effect of the catalyst on toluene was clarified.
[0065] Figure 3 The graph shows a comparison of the catalytic effects of the catalysts prepared in Examples 1 to 3 and Comparative Example 1.
[0066] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing carbon nanotube-based ternary adsorption catalytic materials through in-situ synthesis in a photofluidized bed, comprising the following steps: Step 1: Oxidation modification of carbon nanotube surface Purified carbon nanotubes were dispersed in an aqueous hydrogen peroxide solution, soaked and stirred at room temperature, and then filtered and dried to obtain modified carbon nanotubes (CNTs) for later use. The etching effect of hydrogen peroxide was used to introduce hydroxyl and carboxyl oxygen-containing functional groups in situ into the CNT tube wall, providing uniform anchoring points for the metal precursor and improving the binding strength of the active components. Step 2: Active layer of Ti substrate loaded in optical fluidized bed (2.1) Preparation of precursor solution: Mix Ti(OH)4 solution with hydrogen peroxide aqueous solution to prepare a homogeneous and stable Ti-hydrogen peroxide complex solution; then add the modified carbon nanotube powder obtained in step 1) and stir to form a precursor mixture; (2.2) In-situ photocuring: The precursor mixture obtained in step 2.1) is added to a fluidized bed chamber equipped with an ultraviolet light source. The fluidizing gas is turned on to keep the precursor powder in a suspended fluidized state. During the fluidization process, the light is continuously irradiated simultaneously. The precursor undergoes photo-oxidation reaction in situ on the CNT tube wall, and the nano-TiO2 is uniformly anchored on the surface of the carbon nanotube, effectively avoiding particle agglomeration. After the fluidized light irradiation reaction for 1~2 hours, CNT@TiO2 intermediate powder is obtained. Step 3: Co-loading Ce and Pd components in an optical fluidized bed to synthesize a Ti-Ce-Pd ternary composite adsorption catalytic material. (3.1) Preparation of Ce-Pd precursor: Ce precursor and Pd precursor were mixed in hydrogen peroxide aqueous solution and stirred evenly. The CNT@TiO2 intermediate powder dispersion system prepared in step 2) was added to it and mixed to obtain CNT@TiO2-Ce-Pd composite precursor. (3.2) Secondary photofluidized bed loading: The above precursor is added to the photofluidized bed cavity and kept in a suspended fluidized state. It is simultaneously illuminated throughout the process to induce in-situ deposition. The fluidized light reaction lasts for 1-2 hours. The light excites hydrogen peroxide to generate active free radicals, which promote the in-situ conversion of Ce-Pd precursor into nano Pd and cerium oxide, and uniformly coats and anchors them on the TiO2 surface to form a tightly coupled Ti-Ce-Pd ternary composite nano active layer, and finally obtains the target product.
2. The preparation method according to claim 1, characterized in that, Preferably, in step 1), the solid-liquid ratio of carbon nanotubes to H2O2 is 1:0.5 to 1:10, more preferably 1:0.5 to 1:5, and even more preferably 1:1; Preferably, the mass percentage concentration of the hydrogen peroxide aqueous solution in step 1) is 20% to 30%, more preferably 25%; Preferably, the soaking and stirring time in step 1) is 2-4 hours.
3. The preparation method according to claim 1, characterized in that, Preferably, in step 2.1), the molar ratio of Ti(OH)4 to H2O2 is 1:5 to 1:50, more preferably 1:10 to 1:30, and even more preferably 1:20; Preferably, the mass percentage concentration of the Ti(OH)4 solution in step 2.1) is 3% to 15%, more preferably 6.5% to 7.5%; Preferably, in step 2.1), the solid-liquid ratio of the modified CNT to the precursor liquid is 1:1 to 1:30, more preferably 1:1 to 1:5, and even more preferably 1:2.
5.
4. The preparation method according to claim 1, characterized in that, Preferably, the fluidizing gas used in step 2.2) is air or nitrogen; Preferably, the ultraviolet irradiation conditions in step 2.2) are 254 nm and 0.1 mW / cm². 2 Up to 1.5mW / cm 2 Continuous exposure to ultraviolet light; Preferably, in step 2.2), the temperature of the entire reaction system is controlled to be less than or equal to 80°C, and more preferably between 40°C and 80°C.
5. The preparation method according to claim 1, characterized in that, Preferably, the Ce precursor in step 3.1) is selected from Ce(OH)4, hydrochloride, and nitrate; Preferably, the Pd precursor in step 3.1) is selected from hydrochloride, nitrate, and sulfate; Preferably, in step 3.1), the molar ratio of Ce:Pd:H2O2 is 0.1-10:0.1:10-50, more preferably 1-10:0.1:10-40, and even more preferably 5:0.1:20; Preferably, the solid-liquid ratio of the CNT@TiO2 intermediate powder added in step 3.1) to the system is 1:1 to 1:10, more preferably 1:1 to 1:5, and more preferably 1:2.
5.
6. The preparation method according to claim 1, characterized in that, Preferably, the fluidizing gas used in step 3.2) is air or nitrogen; Preferably, the ultraviolet irradiation conditions in step 3.2) are 254 nm and 0.1 mW / cm². 2 Up to 1.5mW / cm 2 Continuous ultraviolet light irradiation, with a light intensity preferably of 0.1 mW / cm². 2 Up to 0.8mW / cm 2 More preferably 0.4 mW / cm 2 ; Preferably, in step 3.2), the temperature of the entire reaction system is controlled to be less than or equal to 80°C, and more preferably between 40°C and 80°C.
7. A carbon nanotube-based ternary adsorption catalyst, said catalyst being prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the carbon nanotube-based ternary adsorption catalyst according to claim 7, characterized in that, The application is for the catalytic degradation of large-volume, low-concentration VOC waste gas from petrochemical plants.
Citation Information
Patent Citations
Modified carbon nanotube supported metal hydrogenation catalyst and preparation method and application thereof
CN121060516A
Carbon nano tube loaded ternary PtCoNi composite catalyst as well as preparation method and application thereof
CN121983599A